(untitled) (EU and comparative law issues and challenges series (ECLIC), 2022)
Authors are analysing the extent of acceptance of rule on mandatory presence of two witnesses during a home search in national criminal proceedings in EU Member States. While some police powers in Croatia are regulated using modern forms of protection of suspects’ rights, some other investigative actions are regulated using rules that are uncommon in EU. Home search has a historic model of obligatory presence of two witnesses. These witnesses are often randomly selected among citizens, they are not legal professionals. A suspect has no right to reject witnesses if he considers that they could violate his privacy or health rights. Besides that, the Two-witness Rule has a peculiar impact on the evidence law. Items found during home search cannot be legally used if only one witness was present. According to such consequence, this rule actually requires a certain number of witnesses to prove a fact. Such requirements on number of witnesses have been abandoned in modern evidence law. The results of the analysis of the EU Member States show that the rule on the mandatory presence of two witnesses is widespread only in some post-communist systems. When it comes to EU criminal procedure codes (CPCs), the mandatory presence of witnesses exists in Croatian, Slovenian and Bulgarian CPC. The study is showing influence of former Russian CPC in post-Soviet era as well as the influence of former Yugoslav CPC. Regarded as the relic of the past, these procedural guarantees of home inviolability in the cases of home search should be reassessed and improved. In the context of COVID crisis, mandatory presence of witnesses presents challenge for the protection of suspect’s and witnesses’ health. Observed from the suspect’s right to protect his health or the witnesses’ right not to expose themselves to potentially health endangered situations, finding witnesses presents even more complexed mission. If the suspect is in COVID quarantine and the search must be conducted, can witnesses be forced to enter such premises? In case that suspect requires fully vaccinated witnesses who can present valid COVID Certificate or negative PCR test, how could his requirement be fulfilled? The possible solution for both evidence law and health reasons could be the use of modern technologies such as video recording that could replace mandatory witnesses presence. Finally, it would be more appropriate to respect the suspect’s choice on protection of his rights or to use modern technical means or defence lawyer, as in other investigative actions in criminal procedure.